Formation and Development of Cultural Competence by Increasing Access to Material Forms of Historical and Art-History Heritage - Chmil, Hanna; Zubavina, Iryna; Kupriichuk, Vasily; Kuznietsova, Inna; Mishchenko, Maryna (International Journal of Criminology and Sociology, 2021)
The formation of the practical competence of the cultural cycle is determined, first of all, by the formation of access to the fund of material and non-material forms of art, which makes it possible to expand the possibilities of an individual to increase his cultural level. The relevance of the study is determined primarily by the fact that each individual must not only carry out his practical activities but also form an understanding of the meaning of cultural studies in his mind. In this regard, and in the context of overcoming crisis phenomena in the economy, turning to non-material forms becomes a priority task for bearers. The novelty of the research is determined by the possibilities of increasing access to cultural products, while the importance of access is determined not only by high culture. The authors show that the ability to access forms of mass culture also matters. It is shown that one of the possibilities of access to popular culture is to increase the level of distribution of library access. Using the example of countries that declare their commitment to raising the cultural level of the population, the necessity for the development of digital educational resources is shown. The practical significance of the study is determined by the possibilities of widely involving the population in the processes of digitalisation of information carriers about art and, on the basis of this, about the formation of general cultural competence in society as a whole.